Assessing Monitoring and Evaluation Systems in Philippine Local Government Units: A Study of Cavite LGUs - Buenaflor, EnP Katherine B. (International Journal of Research in Interdisciplinary Studies, 2024)
This study investigates the implementation of monitoring and evaluation (M&E) systems in Philippine Local Government Units (LGUs) through the lens of Good Governance Theory [1]. Recognizing the pivotal role of M&E in assessing the effectiveness and impact of LGU programs, projects, and policies [2], this research examines the alignment between M&E practices and the principles of good governance — participation, rule of law, transparency, responsiveness, consensus orientation, equity, effectiveness, efficiency, accountability, and strategic vision [1]. Despite the acknowledged importance of M&E, a significant proportion of LGUs in the Philippines prioritize M&E poorly [3], raising concerns about the factors influencing its implementation. This study delves into the extent to which good governance principles are reflected in LGU M&E practices, the challenges and barriers hindering effective implementation, and the influence of good governance alignment on the effectiveness of LGU initiatives. Ultimately, this research aims to derive policy recommendations that can bolster M&E capacity and foster a culture of evidence-based decision-making within Philippine LGUs [4]. By addressing the existing gaps in M&E implementation, this study seeks to enhance the overall effectiveness and impact of local governance in the Philippines.